'We Are Not Junkies': Bridging Religious and Cultural Barriers to Substance Abuse Mitigation - Armstrong, Chanda (Lembaga Yasin AlSys, 2026)
Substance abuse is a significant public health issue that affects individuals and communities by undermining social, economic, financial, spiritual, and psychological well-being. However, religious and cultural beliefs and practices may hinder the effectiveness of substance abuse interventions, particularly when stigma, misconceptions about faith-based healing, and structural barriers limit access to treatment. This study aims to examine the complex relationship among culture, religion, and substance abuse mitigation and to identify culturally sensitive strategies for improving prevention and intervention efforts. A qualitative approach was employed through literature review, document analysis, and case study review, with ecological systems theory used to emphasize the importance of incorporating community perspectives into intervention design. The findings indicate that cultural norms, religious beliefs, and traditional practices can function both as barriers to substance abuse mitigation and as potential resources for developing contextually relevant prevention and treatment strategies. Barriers to treatment are closely linked to societal stigma, misconceptions surrounding faith-based healing, and broader structural challenges within affected communities. The study concludes that substance abuse mitigation requires tailored intervention strategies that bridge cultural and religious divides while aligning with the values of impacted populations. This study contributes to public health and community intervention literature by highlighting the need for culturally responsive approaches that address stigma, strengthen community engagement, and improve the effectiveness of substance abuse prevention and treatment efforts.